Salons Contrastés 1902-1982 : De Matisse à Warhol : Acquisitions récentes. - Jaguer, Edouard (Paris : Galerie 1900-2000, 1985)
Bandeira, Antonio ; Ben ; Bott, Francis ; Brassaï ; Alverez Bravo, Manuel ; Cesar ; Coutaud, Lucien ; Crepin, Joseph ; Donati, Enrico ; Ernst, Max ; Hager, Anneliese ; Hantaï, Simon ; Helion, Jean ; Henry, Maurice ; Hugo, Valentine ; Laloy, Yves ; Man Ray ; etc.
Salons Contrastés 1902-1982 : De Matisse à Warhol : Acquisitions récentes, Galerie 1900-2000, Paris, 15.03 - 30.04.1985
boek